The Role of Motivation in Influencing Student Success in Learning - Thessia Permata Bunda; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to examine learning motivation. This research is research usih the literature review method, namely by searching for literature from various books and articles related to the topic discusses with the keyword learning motivation. Based on research results, motivation is one of the factors that can influence students succes in learning. Motivation can provide enthusiasm, enthusiasm and a sense of enjoyment in learning activities, students whohave high motivation will have the energy to participate in learning activities.